1998
DOI: 10.1136/fn.78.2.f99
|View full text |Cite
|
Sign up to set email alerts
|

Increased survival and deteriorating developmental outcome in 23 to 25 week old gestation infants, 1990-4 compared with 1984-9

Abstract: Aims-To assess whether changes in survival over time in infants of 23 to 25 weeks of gestational age were accompanied by changes in the incidence of disability in childhood during an 11 year period. Methods-Obstetric and neonatal variables having the strongest association with both survival to discharge from a regional neonatal medical unit and neurodevelopmental disability in 192 infants of 23 to 25 weeks of gestation, born in 1984 to 1994, were studied as a group and in two cohorts (1984 to 1989 n = 96 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
3
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 12 publications
7
72
3
6
Order By: Relevance
“…9 Over recent years, trials focused on evaluating the prognosis for child development have generally been conducted in developed countries and have included infants with birth weight under 1500 g, and particularly those with less than 32 weeks of gestation. [25][26][27] However, whether low birth weight is due to prematurity or IGR, it constitutes a risk factor for developmental abnormalities. This association is particularly frequent under unfavorable social conditions.…”
Section: Resultsmentioning
confidence: 99%
“…9 Over recent years, trials focused on evaluating the prognosis for child development have generally been conducted in developed countries and have included infants with birth weight under 1500 g, and particularly those with less than 32 weeks of gestation. [25][26][27] However, whether low birth weight is due to prematurity or IGR, it constitutes a risk factor for developmental abnormalities. This association is particularly frequent under unfavorable social conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A rise in neonatal morbidity and later disability in childhood with improved survival leading to no significant change in the number of normal survivors (16% vs 14%) as the proportion of the original population was observed recently as an alarming development comparing the outcome of 192 EPT infants in a large single-center study during an 11-year period. 34 Near universal initiation of intensive care in a population-based cohort of EPT infants (23)(24)(25)(26) weeks' gestation) who were born during the mid1980s in central New Jersey (n ϭ 146), compared with selective initiation of intensive care for a comparable group of EPT infants in the Netherlands (n ϭ 141),…”
Section: Discussionmentioning
confidence: 99%
“…9,21,23,28 -30 More active treatment, ie, cesarean section and active resuscitation, of these infants does not always improve the outcome, 30 although surfactant treatment has been found beneficial. 31 The study by Emsley et al 9 showed improved survival of infants born at 23 to 25 GWs between 1984 and 1994 but showed a significant rise in disability rates. The deteriorated outcome was primarily caused by visual impairments, whereas the incidence of cerebral palsy remained constant.…”
Section: Figmentioning
confidence: 99%
“…Thus, the total number of children born extremely immature and surviving with long-term disability increased. 8,9 During the 1990s, new advances in care, such as antenatal steroid treatment to mothers with threatening premature labor, surfactant treatment to infants with respiratory distress syndrome (RDS), and new modes of respiratory support, all known to decrease the mortality of ELBW infants, have become widely used in developed countries. From this period, there are scarce data on long-term follow-up.…”
mentioning
confidence: 99%